Selection of Proteolytic Lactic Acid Bacteria with Probiotic Properties for Fish Protein Hydrolyzate Production - Deford Cristy Birahy; Titi Candra Sunarti; Anja Meryandini (Jurnal Ilmu Pertanian Indonesia, 2025)
This study aimed to select a proteolytic LAB with probiotic properties that can be applied to manufacture protein hydrolysate from fish heads. Tests on 20 isolates of LAB showed that nine isolates were proteolytic and non-pathogenic. A total of 5 isolates could grow well at 0.5% bile salt stress, and 3 of them could grow at pH 3. These three isolates had antagonistic ability against Salmonella bacteria, and one isolate was sensitive to the antibiotic tested. Molecular identification of the selected LAB isolates showed a 100% sequence similarity with Pediococcus pentosaceus with accession number MT515895.1. The LAB isolate has high proteolytic activity since it can increase the soluble fraction of fish meal powder from 32.10% to 88.38% in 48 hr. Production of protein hydrolysate using tuna waste was carried out for 30 days. Tuna waste protein hydrolysate had a medium antioxidant activity of 25.57 ± 0.93%. The hydrolyzed protein comprised 17 amino acids, including nine non-essential and eight essential amino acids, and is dominated by glutamic acid. Selected LAB isolate is potentially used in protein hydrolysate production, especially for flavor enhancers. Keywords: antagonistic, amino acid, Pediococcus pentosaceus